PENURUNAN NYERI DAN DISABILITAS DENGAN INTEGRATED NEUROMUSCULAR INHIBITION TECHNIQUES (INIT) DAN MASSAGE EFFLEURAGE PADA MYOFASCIAL TRIGGER POINT SYNDROME OTOT TRAPESIUS BAGIAN ATAS - Veni Fatmawati (Sport and Fitness Journal, 2013)
Myofascia Trigger Point Syndrome (MTrPs) is trigger point muscle happens in musculoskeletal. Factors which strengthen and trigger the emerge of MTrPs are the muscle contraction which happens continuously, poor body position, wrong body position or movement, poor occupation activity and unsuitable workplace arrangement that affect the unergonomic work behavior. The objective of this reseacrh is to reveal the effectivity of  integrated neuromuscular  inhibition techniques (init ) and massage efflurage in decreasing pain and disability in myofasial trigger point of upper trapesius muscle. The subjects this research are 34 people which are taken randomly in Puskesmas 2 Kartosuro, Surakarta with 17 samples of each group. Group 1 is integrated neuromuscular inhibition techniques (init ) and group 2 is massage efflurage. The data used in this research is NDI scale taken before and after therapy. The data collected is processed by using differential test through computer base of SPSS 15.0 version. The data analysis by using paired sample t-test, in group 1 the data resulted before therapy is 48,35±6,68 and the data resulted after therapy is 25,94±5,87 with p = 0,000 (p < 0,05). Whereas in group 2, the  resulted before therapy is 47,53±5,17 and the data resulted before therapy is 28,00±8,91 with p = 0,000 (p < 0,05). To conclude, based on the data resulted in this research, integrated neuromuscular  inhibition techniques (init ) and massage effleurage are there is no difference decrease pain and disability in myofascial trigger point of upper trapezius muscle.